2020
DOI: 10.1038/s41598-020-76092-4
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity indicating the threatened status of Rhizophora apiculata (Rhizophoraceae) in Malaysia: declined evolution meets habitat destruction

Abstract: Worldwide, many mangrove species are experiencing significant population declines, including Rhizophora apiculata, which is one of the most widespread and economically important species in tropical Asia. In Malaysia, there has been an alarming decline in R. apiculata populations driven primarily by anthropogenic activities. However, the lack of genetic and demographic information on this species has hampered local efforts to conserve it. To address these gaps, we generated novel genetic information for R. apic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
(65 reference statements)
3
23
0
Order By: Relevance
“…Inbreeding and genetic diversity that are common to mangrove populations were also observed for A. marina (Maguire et al, 2000b;Dodd et al, 2002;Yan et al, 2016). Therefore, continued monitoring and in-depth research are necessary to provide further scientific insights on this population diversity, especially from the areas like Malay Peninsula where land blockage effect is protuberant (Azman et al, 2020;Wee et al, 2020;Fairuz-Fozi et al, 2021).…”
Section: Discussion Evolutionary Significant Units and Hybridizationmentioning
confidence: 98%
“…Inbreeding and genetic diversity that are common to mangrove populations were also observed for A. marina (Maguire et al, 2000b;Dodd et al, 2002;Yan et al, 2016). Therefore, continued monitoring and in-depth research are necessary to provide further scientific insights on this population diversity, especially from the areas like Malay Peninsula where land blockage effect is protuberant (Azman et al, 2020;Wee et al, 2020;Fairuz-Fozi et al, 2021).…”
Section: Discussion Evolutionary Significant Units and Hybridizationmentioning
confidence: 98%
“…The change in genetic diversity diagnosed by the excess of homozygotes can be related to habitat destruction due to anthropogenic means and the subsequent inbreeding. Human activities such as logging and developments near mangrove habitats can disrupt the gene flow leading to population size reduction ( Azman et al., 2020 ). Spatial genetic structure analysis among populations of A. germinans and R. mangle of Pacific and Caribbean coastal lines revealed significant differences in genetic structure of estuaries from the same coastline, while A. germinans showed higher levels of genetic diversity as compared to R. mangle.…”
Section: Mangrove Conservation For the Prevention Of Genetic Erosionmentioning
confidence: 99%
“…Exploiting mangrove habitats by largely converting them into aquaculture ponds for fish, shellfish, and shrimp farming could reduce mangrove areas, alter the hydrology, and eventually cause eutrophication ( Friess et al., 2019 ; Hong et al., 2018 ). The other deteriorative effects of human activities such as logging and developments near mangrove habitats impart long-term consequences by acting as a barrier of gene flow resulting in low genetic diversity ( Azman et al., 2020 ; Meng et al., 2016 ). Microsatellite studies on Rhizophora apiculata serve as a typical example of a similar situation which revealed low genetic diversity among the populations and reduction in population size due to habitat fragmentation ( Azman et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with those reported by Panda et al (2015) on Plumbago zeylanica L. plants in which fragmented populations have lower genetic diversity values than other populations that are not fragmented. According to Azman et al (2020) that populations that have low genetic diversity values indicate that these populations are in a condition of threatening, fragmented, and damaged by human activities. In contrast, The high genetic diversity in the Pokomo population could be caused by several factors, namely i) the genetic diversity has been high from the beginning of the population established, ii) the population has not been a lot disturbed by human activities, so its condition is more maintained, and iii) the occurrence of random mating among individuals resulting in genetic recombination and increasing genetic diversity within population.…”
Section: Genetic Diversity Within Populationsmentioning
confidence: 99%